Consciousness as a Physical Process Caused by the Organization of Energy in the Brain - Pepperell, Robert (Frontiers in Psychology, 2018)
To explain consciousness as a physical process we must acknowledge the role energy plays in the brain. Energetic activity is fundamental to all physical processes and causally drives biological behaviour. Recent neuroscientific evidence can be interpreted in a way that suggests consciousness is a product of the organization of energetic activity in the brain. The nature of energy itself, though, remains largely mysterious, and we do not fully understand how it contributes to brain function or consciousness. According to the prin-ciple outlined here, energy, along with forces and work, can be described in terms of actu-alized differences of motion and tension. By observing physical systems, we can infer there is something it is like to undergo states of actualized difference from the intrinsic perspective of the system. Consciousness occurs because there is something it is like, in-trinsically, to undergo a certain organization of actualized differences in the brain.